PENERAPAN PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN (PJOK) DI SMK NEGERI 1 KABANJAHE - Barus, Julius Boy Nesra Basgimata; Sinuraya, Janwar Frihasan; Sitepu, Terangta (JURNAL CURERE, 2023)
The scientific approach is a learning model using the scientific method in student-centered learning activities (student-centered approach). The scientific approach aims to be able to have capabilities in critical, scientific and analytical thinking skills. The purpose of this study was to determine the implementation of a scientific approach to PJOK learning at SMK Negeri 1 Kabanjahe. This research approach is a qualitative method. Data collection and retrieval was carried out at SMK Negeri 1 Kabanjahe. While the technique of data collection is by interviews and questionnaire assistance. The samples used were 2 PJOK teachers and 124 students who were taught by these teachers. Data analysis techniques used descriptive qualitative analysis techniques including data reduction, data presentation, and drawing conclusions. Based on the results of the study it can be concluded that the PJOK learning approach using a scientific approach at SMK Negeri 1 Kabanjahe is included in the good category of 79.14% seen from lesson planning, learning processes, and assessment of student learning outcomes. Through a scientific approach in learning at school will give students ways to think, behave and innovate in learning.